Spatio-temporal stability of pre-treatment 18F-Fludeoxyglucose uptake in head and neck squamous cell carcinomas sufficient for dose painting. (21st October 2015) - Rasmussen, Jacob H.; Vogelius, Ivan R.; Aznar, Marianne C.; Fischer, Barbara M.; Christensen, Charlotte B.; Friborg, Jeppe; Loft, Annika; Kristensen, Claus A.; Bentzen, Søren M.; Specht, Lena
ABSTRACT: Background. The pre-treatment 18F-Fludeoxyglucose (FDG) avid subvolume of the tumor has shown promise as a potential target for dose painting in patients with in head and neck squamous cell carcinomas (HNSCC). Purpose. The purposes of this study are: 1) to assess the pre-treatment spatio-temporal variability of FDG PET/CT target volumes and 2) to assess the impact of this variability on dose distribution in dose painting plans in patients with HNSCC. Material and methods. Thirty patients were enrolled and scanned twice, three days apart, days prior to treatment. Delineation of the FDG avid subvolume of the tumor and lymph nodes on both scans was performed by a specialist in nuclear medicine yielding GTVPET1 and GTVPET2 and segmentation based on SUV iso-contours were constructed yielding two metabolic target volumes, MTV1 and MTV2. Images were co-registered rigidly and dose painting plans with dose escalation up to 82 Gy to GTVPET1 were planned and GTVPET2 was copied from the co-registered images to the dose planning scan. Variation in dose to the target and modeled tumor control probability were assessed as measures of the impact of imaging variations in a dose painting scenario. Results. Twenty-four patients were available for full analysis. The median mismatch between GTVPET1 and GTVPET2 was 14.2% (1.7 cm 3 ). The median difference in dose to the FDG planning target volume was 0.3 Gy (PTVPET) and 0.4 Gy (PTVMTV). Median difference in the modeled tumor control probability (TCP) was < 0.2% and 23 of 24 patients had a difference in expected TCP < 1%. Conclusions. Pre-treatment FDG PET/CT target volumes were stable and day-to-day variability had no relevant impact on dose distribution and expected tumor control in dose painting plans.